Impact of early prosthetic fitting on psychomotor development of children with unilateral congenital below-elbow deficiency - Tomašević, Maja (Rehabilitacija (Ljubljana), 2016)
Background: The aim of prosthetic fitting and associated (re)habilitation is promotion of functional, psychological, cognitive and social development with the prosthesis as a new biomechanical entity. The primary prosthesis for children with unilateral congenital below-elbow deficiency (UCBED) is aesthetic. It is applied in outpatient setting, usually at the age of 7-9 months, along with developmental physiotherapy. The objective of such an early prosthetic fitting is the timely creation of engrams through early psychomotor development. The large variety of wrist and hand movements with all modes of power, coordination, agility and precision of movement cannot be fully restituted with the prosthesis. Hence, the prosthesis is utilised along with the dominant hand as an aid for fixation and synergy. Methods: A survey was conducted at the Clinical Institute for Rehabilitation and Orthopedic Aids in Zagreb in the period from 2012 to 2015 on 12 children (7 girls and 5 boys) with UCEBED aged 3-5 years, primarily fitted with pasive prosthesis at the age of 7-9 months. Functionality in bimanual activities was tested using the ABILHAND-Kids scale. Self-assessment of body image was performed using a reverse visual analogue scale (VAS). Results: The raw ABILHAND-Kids scores were statistically significantly lower on average when performing functional tasks with the prosthesis as compared to performing them without the prosthesis (mean score 26.1 vs. 30.9, p < 0.001). However, satisfaction with body image related to social acceptance and passive application of prosthesis in everyday life was statistically significantly higher on average with the prosthesis than without it (mean VAS rating 9.8 vs. 3.7, p < 0.001). Conclusion: The comprehensive habilitation of children with a prosthetic limb requires an individual, holistic and team-based problem-oriented approach. It is necessary to enable the child%s freedom of movement and unrestricted play, along with his/her expression of personality, needs, desires and abilities. Early prosthetic fitting, continuous training for carrying out activities appropriate for the given age, involvement of parents and permanent wearing of the prosthesis are the most important factors for the acceptance of pasive prosthesis, which has a significant impact on the normal psychological, social and motor development and growth of the child.
Keywords: amputacija; Child; otroci; Prostheses and implants; proteze; rehabilitacija; rehabilitation; upper limb impairment; vocational rehabilitation; zgornji ud